Letter - Hopcroft, F.
027-0008-001 Brentford & Chiswick Trades' Council. Secretary: MR. F. HOPCROFT, 7 BRENTWICK GARDENS, BRENTFORD, MX. Sir W.M. Citrine. General Secretary. T.U.C. 18-9-40. Dear Sir, I have enclosed two letters for your information and comments. My Council wish to know if any special arrangements have been made to deal with these Spanish Refugees or are they being dealt with under the general refugee regulations. My Council are of the opinion that some special effort should be made to deal with these friendly Spanish Refugees. I should be pleased to receive letters back. Thanking you Yours fraternally F. Hopcroft Secretary. 292/946/27/8